Tolerance analysis and charting of the sheet metal punch and bending forming process - Han, Stanley Tong Jee. (2008)
This paper discuss the development of a method to analyse the dimension and tolerance of a sheet metal part after undergoing a series of bends and to check whether part specification can be met.